Taxation and the worlds of welfare - Monica Prasad; Yingying Deng (Luxembourg Income Study (LIS), 2008)
We use Luxembourg Income Study data to compare the progressivity of the tax structure in the U.S. and Europe. While our study supports the arguments of other scholars that the US has more progressive taxes than the continental or social democratic countries, we also present the following qualifications: (1) While the US remains more progressive than other countries, since 1991 its tax structure is in fact regressive. All other countries for which it is possible to calculate overall regressivity have always been, and remain, regressive overall. (2) Britain's tax structure is as regressive as Sweden's. (3) It is a mistake to consider particular kinds of taxes (e.g. income or property) as progressive or regressive: there are examples of progressive property and payroll taxes, and regressive income taxes. And (4) the comparative pattern of progressivity is partly the result of the role of the value added tax in the European revenue structure, and the small role that sales taxes play in the U.S. We close with a discussion of whether the regressivity of the value added tax matters, and what agenda for future research our work suggests.
Keywords: H22; P51; I38; 330; taxation; welfare state; capitalist systems; Steuerprogression; Steuertarif; Steuersystem; Umsatzsteuer; Vergleich; EU-Staaten; USA